Effect of weld power and build compliance on ultrasonic consolidation. Issue 2 (21st March 2016) - Hehr, Adam; Wolcott, Paul J.; Dapino, Marcelo J.
Abstract : Purpose: Ultrasonic additive manufacturing (UAM) is a fabrication technology based on ultrasonic metal welding. As a solid-state process, temperatures during UAM fabrication reach a fraction of the melting temperatures of the participating metals. UAM parts can become mechanically compliant during fabrication, which negatively influences the ability of the welder to produce consistent welds. This study aims to evaluate the effect of weld power on weld quality throughout a UAM build, and develop a new power-compensation approach to achieve homogeneous weld quality. Design/methodology/approach: The study utilizes mechanical push-pin testing as a metric of delamination resistance, as well as focused ion beam and scanning electron microscopy to analyze the interface microstructure of UAM parts. Findings: Weld power was found to negatively affect mechanical properties and microstructure. By keeping weld power constant, the delamination energy of UAM coupons was increased 22 per cent along with a consistent grain structure. As a result, to ensure constant properties throughout UAM component construction, maintaining weld power is preferable over the conventional strategy based on amplitude control. Research limitations/implications: Further characterization could be conducted to evaluate the power control strategy on other material combinations, though this study strongly suggests that the proposed approach should work regardless of the metals being welded. Practical implications: The proposed power control strategy can be implemented by monitoring and controlling the electrical power supplied to the welder. As such, no additional hardware is required, making the approach both useful and straightforward to implement. Originality/value: This research paper is the first to recognize and address the negative effect of build compliance on weld power input in UAM. This is also the first paper to correlate measured weld power with the microstructure and mechanical properties of UAM parts.